2007
DOI: 10.1590/s1413-35552007000200005
|View full text |Cite
|
Sign up to set email alerts
|

Redução da variabilidade da freqüência cardíaca em indivíduos de meia-idade e o efeito do treinamento de força

Abstract: Objective: To investigate autonomic modulation of the sinus node, by analyzing heart rate variability (HRV) among young and middle-aged individuals, and to assess the effect of an resistance strength training program on this modulation among middleaged individuals. Method: Thirty-two healthy nonsmoking men with sedentary lifestyles, of whom 10 were young (22.2 ± 1.5 years) and 22 were middle-aged (49.3 ± 5.3 years), underwent electrocardiogram signal acquisition for time-domain HRV analysis. The middle-aged in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
7

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 14 publications
1
9
0
7
Order By: Relevance
“…Lopes et al, (2007) [14] found in their study that strength training can improve HRV, especially in young people, but that was not seen in the elderly, since variability declines with the physiological process of aging because of depletion of the vagal tonus, increase in the sympathetic activity and the presence of diseases such as hypertension or heart failure.…”
Section: Science Directmentioning
confidence: 98%
“…Lopes et al, (2007) [14] found in their study that strength training can improve HRV, especially in young people, but that was not seen in the elderly, since variability declines with the physiological process of aging because of depletion of the vagal tonus, increase in the sympathetic activity and the presence of diseases such as hypertension or heart failure.…”
Section: Science Directmentioning
confidence: 98%
“…Moreover, these indexes also allow verification of the influence of factors such as age [4,7,37,79,80], gender [81][82][83] and exercise [17][18][19]29,38] on the autonomic control. Table 2 shows studies using HRV in various physiological and pathological conditions.…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…Table 2 shows studies using HRV in various physiological and pathological conditions. Carnethon et al [56] Novais et al [29] Menezes et al [60] Terathongkum et al [61] Takahashi et al [55] Bittencourt et al [26] Pecyna [63] Carney et al [54] Limongelli et al [58] Karas et al [59] Larosa et al [62] Javorka et al [38] Catai et al [7] Weerapong et al [41] Mello et al [37] Paschoal et al [72] Sin DD et al [66] Kudaiberdieva et al [65] Lopes et al [71] Neves et al [73] Furuland et al [68] Lopes et al [79] and Paschoal et al [80] observed that the aging process causes a depletion of vagal tone and consequent increase in sympathetic activity, therefore older individuals have a lower HRV. In 2006, Rajendra Acharya et al [4] observed that HRV is lower with age and the variation is greater in women.…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…In the TD, the RMSSD index, which corresponds to the root mean square of the difference between successive normal adjacent R-R intervals, expressed in milliseconds (ms) 27 and the SDNN index, which corresponds to the standard deviation of all normal sinus R-R intervals, expressed in ms 16 , were used.…”
Section: Linear Analysis Of Hrvmentioning
confidence: 99%